Personality traits and suicidal ideation in students of a national university in Lima - Rodríguez de los Ríos, Luis Alberto (2021)
The main objective of the research was to establish the relationship between personality traits and suicidal ideation in university students from the city of Lima. The methodological approach used was the quantitative, non-experimental method, and a correlational descriptive design. The study sample consisted of 384 students of both sexes, to whom the Reduced Personality Inventory of Five Factors (NEO-FFI) by Paul Costa (Jr.) & Robert McCrae (2008) and the Suicidal Ideation Scale were applied. de A, Beck, M, Kovacs and A. Weissman (2004). The results obtained showed that there is a significant relationship between personality traits and suicidal ideation in the studied sample, this being a medium or moderate positive correlation, according to the correlation indices (r = 0.433).